Access to Care and Cardiovascular Disease Prevention. Issue 34 (August 2015) - Alcalá, Héctor E.; Albert, Stephanie L.; Roby, Dylan H.; Beckerman, Jacob; Champagne, Philippe; Brookmeyer, Ron; Prelip, Michael L.; Glik, Deborah C.; Inkelas, Moira; Garcia, Rosa-Elenna; Ortega, Alexander N.; Luis, Pinet Peralta.
<x xml:space="preserve">Abstract</x> Abstract Cardiovascular disease (CVD) is the leading killer of Americans. CVD is understudied among Latinos, who have high levels of CVD risk factors. This study aimed to determine whether access to health care (ie, insurance status and having a usual source of care) is associated with 4 CVD prevention factors (ie, health care utilization, CVD screening, information received from health care providers, and lifestyle factors) among Latino adults and to evaluate whether the associations depended on CVD clinical risk/disease. Data were collected as part of a community-engaged food environment intervention study in East Los Angeles and Boyle Heights, CA. Logistic regressions were fitted with insurance status and usual source of care as predictors of the 4 CVD prevention factors while controlling for demographics. Analyses were repeated with interactions between self-reported CVD clinical risk/disease and access to care measures. Access to health care significantly increased the odds of CVD prevention. Having a usual source of care was associated with all factors of prevention, whereas being insured was only associated with some factors of prevention. CVD clinical risk/disease did not moderate any associations. Although efforts to reduce CVD risk among Latinos through the Affordable Care Act could be impactful, they might have limited impact in curbing CVD among Latinos, via the law's expansion of insurance coverage. CVD prevention efforts must expand beyond the provision of insurance to effectively lower CVD rates.